The Labor Market Effects of Venezuelan Migration in Ecuador - Olivieri, Sergio; Ortega, Francesc; Carranza, Eliana; Rivadeneira, Ana (World Bank, Washington, DC, 2020)
As of 2019, more than 1.2 million Venezuelans passed through Ecuador and more than 400,000 settled (almost 3 percent of Ecuador's population). This paper analyzes the location choices of Venezuelan migrants in Ecuador and the labor market consequences of these choices, using data from Ecuador's labor force survey and mobile phone records on the geographic distribution of Venezuelan migrants. Around half of the migrants live in four cantons (of 221). Their location is primarily driven by local economic conditions, rather than point of entry. Overall, the regions with the largest inflows of Venezuelans have not seen any effects on labor market participation or employment, compared with regions with fewer inflows. However, our difference-in-difference estimates clearly indicate that young, low-educated Ecuadoran workers in high-inflow regions have been adversely affected. Specifically, the estimates that these workers have experienced reductions in employment quality, a 5 percentage-point increase in the rate of informality, and a 13 percentage-point reduction in earnings, relative to workers with similar characteristics living in areas with very low or non-existent inflows of Venezuelans.